Strategy Development in Moral Aqidah Learning Media - Waqfin, Mohammad Saat Ibnu; Sholihah, Siti (SCHOOLAR: Social and Literature Study in Education, 2024)
The teacher has a very important responsibility in education, this is inseparable from the teacher's own strategy. Effective and efficient strategies make the learning environment more enjoyable and involve students in understanding the material presented. Because the teacher is responsible for the intellectual life of students. The purpose of this study was to find out the implementation of the Post-Pandemic Aqidah Akhlak learning strategy as well as the supporting and inhibiting factors of this learning strategy. The approach used to achieve the above objectives is by using a qualitative research approach with a type of field study research. In collecting data the author uses the method of observation, interviews, and documentation. The results of the study show that: 1). The implementation of the learning strategies used by post-pandemic Aqidah Akhlak subject teachers is more directed at contextual learning strategies. 2). Factors supporting the implementation of the Aqidah Akhlak learning strategy, namely the intelligence of students, the ability of educators, the completeness of the library, infrastructure, available media, and the surrounding environment. While the inhibiting factor is that students pay less attention to the learning process conveyed by the teacher directly and sometimes most students also don't focus on listening to the subject matter, coupled with students who are lazy to do the assignments given by the teacher.